A global evaluation of the effectiveness of voluntary REDD+ projects at reducing deforestation and degradation in the moist tropics. Issue 6 (8th September 2022) - Guizar‐Coutiño, Alejandro; Jones, Julia P. G.; Balmford, Andrew; Carmenta, Rachel; Coomes, David A.
Abstract: Reducing emissions from deforestation and forest degradation (REDD+) projects aim to contribute to climate change mitigation by protecting and enhancing carbon stocks in tropical forests, but there have been no systematic global evaluations of their impact. We used a new data set for tropical humid forests and a standardized evaluation approach (based on pixel matching) to quantify the performance of a representative sample of 40 voluntary REDD+ projects in 9 countries certified under the Verified Carbon Standard (VCS). In the first 5 years of implementation, deforestation within project areas was reduced by 47% (95% confidence interval [CI]: 24–68) compared with matched counterfactual pixels, and degradation rates were 58% lower (95% CI: 49–63). Reductions were small in absolute terms but greater in sites located in high‐deforestation settings and did not appear to be substantially undermined by leakage activities in forested areas within 10 km of project boundaries. At the 26th Conference of the Parties of the United Nations Framework Convention on Climate Change, the international community renewed its commitment to tackling tropical deforestation as a nature‐based solution to climate change. Our results indicate that incentivizing forest conservation through voluntary site‐based projects can slow tropical deforestation and highlight the particular importance of prioritizing financing for areas at greater risk of deforestation. Abstract : Evaluación Global de la Efectividad de proyectos REDD+ en la Reducción de la Deforestación y Degradación en el Trópico Húmedo Resumen: Los proyectos para la reducción de emisiones derivados de la deforestación y degradación de bosques (REDD+) tienen como meta contribuir a la mitigación del cambio climático al protejer y fomentar la disponibilidad de carbono en bosques tropicales, pero a la fecha no se han realizado evaluaciones globales sistemáticas sobre su impacto. Utilizamos bases de datos recientes sobre bosques tropicales húmedos y un método estandarizado de evaluación (basado en 'emparejamiento' [matching] de pixeles) para cuantificar el desempeño de una muestra representativa de 40 proyectos voluntarios REDD+, localizados en 9 países y certificados bajo el estándar Verified Carbon Standard (VCS). En los primeros 5 años de implementación, la deforestación en las áreas de los proyectos disminuyó en 47% (IC 95% 24–68) en comparación con los pixeles contrafactuales correspondientes, y las tasas de degradación fueron 58% menos (IC 95% 49–63). Las reducciones fueron pequeñas en términos absolutos pero mayores en sitios con tasas de deforestación elevadas, y no parecieron ser afectadas sustancialmente por efectos de fuga (leakage) en áreas boscosas en un radio de 10 km de los límites del proyecto. En la COP26, la comunidad internacional renovó su compromiso de afrontar la deforestación tropical como una solución al cambio climático basada en la naturaleza. Nuestros resultados indican que incentivar la conservación de bosques mediante proyectos locales voluntarios puede disminuir la deforestación tropical, y resaltan la importancia de priorizar financiamiento en áreas con un mayor riesgo de deforestación. 【摘要】: 随着世界范围内人类与野生动物的冲突不断升级, 对野生动物的宽容和接纳等概念变得越来越重要。然而, 当代保护研究表明, 人们对人类与野生动物积极互作的认识有限, 导致可能难以准确描述人类与动物的相遇。如果不解决这些局限性, 就会导致野生动物和景观管理计划的设计和实施存在不足, 以及对本土生态知识的否定。我们利用印度喀拉拉邦瓦亚纳德野生动物保护区森林中的阿迪瓦西族Kattunayakans部落的民族志证据, 来研究印度原住民对于人类与野生动物共存的观点。通过定性的实地研究(包括访谈和在森林样带调查), 我们发现Kattunayakans部落表现出对野生动物的宽容和接纳, 其特点是深入的共存, 包括三个中心思想:野生动物是有理性的交流者;野生动物是神、老师和平等的族群;野生动物是实行 " dharmam "的具有共同起源的亲戚。我们认为, 充分理解以上几点有助于将Kattunayakan部落的观点引入印度的森林管理, 并更广泛地解决人类与野生动物的冲突。